Redefining ALL classification: toward detecting high-risk ALL and implementing precision medicine - Hunger, Stephen P; Mullighan, Charles G (Blood, 2015)
Acute lymphoblastic leukemia (ALL) is the commonest childhood tumor and remains a leading cause of cancer death in the young. In the last decade, microarray and sequencing analysis of large ALL cohorts has revolutionized our understanding of the genetic basis of this disease. These studies have identified new ALL subtypes, each characterized by constellations of structural and sequence alterations that perturb key cellular pathways, including lymphoid development, cell-cycle regulation, and tumor suppression; cytokine receptor, kinase, and Ras signaling; and chromatin modifications. Several of these pathways, particularly kinase-activating lesions and epigenetic alterations, are logical targets for new precision medicine therapies. Genomic profiling has also identified important interactions between inherited genetic variants that influence the risk of leukemia development and the somatic genetic alterations that are required to establish the leukemic clone. Moreover, sequential sequencing studies at diagnosis, remission, and relapse have provided important insights into the relationship among genetic variants, clonal heterogeneity, and the risk of relapse. Ongoing studies are extending our understanding of coding and noncoding genetic alterations in B-progenitor and T-lineage ALL and using these insights to inform the development of faithful experimental models to test the efficacy of new treatment approaches.